Postcolonial theology - Haker, Hille; Susin, Luiz Carlos; Messi Metogo, Eloi (Concilium, 2013)
Editorial: Postcolonial theology -- Part One: Contexts of postcolonial theology: Epistemological dissonance: decolonizing the postcolonial theological canon / Joseph Duggan -- The epistemological decolonization of theology / Enrique Dussel -- The politics of othering in North America and the Book of Judges / Uriah Kim -- A postcolonial spectrality of the Cross / Wohnee Anne Joh -- Flesh of the world / Mayra Rivera -- Theology from a space where postcolonialism and theology intersect / Namsoon Kang -- Latin American perspectives on postcolonialism -- Nefertiti's long shadow: postcolonial theory and theology in Germany / Michael Nausner -- Postcolonial theology in an African context / Eloi Messi Metogo -- Part Two: Theological Forum: Liberation theology looks to the future / Agenor Brighenti -- 'Doing' liberation theology from within the margins / Karen Ross -- Margaret Farley, the Vatican and Just Love / Susan A. Ross -- The resignation of Pope Benedict XVI / Felix Wilfred